Transition into remote and rural nurse education and careers: a qualitative study of student nurses - Kyle, Richard G (J Res Nurs, 2020)
BACKGROUND: Global nurse shortages present a threat to the sustainability of remote and rural healthcare. Interventions have been developed to support recruitment and retention of nurses that focus on providing pre-nursing experience for school pupils who intend to pursue nursing careers. However, there is a lack of evidence around how pre-nursing experience supports transition into nurse education. AIMS: This study aims to explore the impact of a pre-nursing scholarship for school pupils in remote and rural areas of Scotland on experiences of transition into nurse education. METHODS: This was a qualitative study involving semi-structured telephone and face-to-face interviews with pre-nursing scholarship participants. RESULTS: An authentic pre-nursing experience supported school pupils’ transition to nurse education. First, it increased students’ self-efficacy, both in their decision to choose nursing as a career and their ability to nurse. Second, it helped students to realise that the opportunity to study closer to home was available to them. Third, it supported students’ educational and social integration, helping them feel prepared for university teaching and learning approaches and the social experience of being a student. CONCLUSIONS: Pre-nursing experience can support transition into nurse education and contribute to career pathways that support recruitment and retention of nurses in remote and rural areas.